The Effectiveness of Using Photograph in Teaching Writing - Megawati Megawati; Syarif Agussaid Alkadrie (JETL (Journal of Education, Teaching and Learning), 2017)
This research entitled: “The Effectiveness of Using Photograph in Teaching Writing” is intended to find out whether there is significantly different in writing ability between the experimental group and the control group.This research employed experimental design. The participants of the study were the tenth-grade students at SMAN 1 Karau Kuala in the academic year 2013/2014. Two classes were used in this research. There were X-C as the Experimental group and X-D as the control group. The research instrument used was a writing test in the form of essay test. The data in this research were mainly gathered through the use of pre-test and post-test. The data were analyzed by measuring t-test and SPSS program to calculate the t-value from the score. The finding of the research shows that there is a significant difference between teaching writing by using photograph and teaching writing without using photograph. After the treatments, the mean is 75.43 the standard deviation is 9.370 the df is 44, and the significance is 0.00. If the significance is smaller than 0.05, it means there is a significant difference between teaching writing by using photograph and teaching writing without using photograph.